Chemoprophylaxis Versus Immunoprophylaxis In Tuberculosis And Leprosy Infection - Bernadette Dian Novita (JURNAL WIDYA MEDIKA, 2020)
Tuberculosis (TB) and leprosy are mycobacterial diseases that still represent significant public health challenges. Bacille Calmette–Guérin (BCG), the only available TB and Leprosy vaccine use as Immunoprophylaxis and has already given in infants. However, the evidence of TB and Leprosy infection in Indonesia remain high. In the last 10 years, chemoprophylaxis for both TB and leprosy were extensively done. However the effectiveness between immunoprophylaxis and chemoprophylaxis remains unclear.